Bioenergy and agriculture: Promises and challenges: Overview - Hazell, Peter B. R.; Pachauri, R. K. (International Food Policy Research Institute, 2006)
In recent years bioenergy (see box for definitions) has drawn attention as a sustainable energy source that may help cope with rising energy prices, address environmental concerns about greenhouse gas emissions, and offer new income and employment to farmers and rural communities around the world. For many countries in the Organisation for Economic Cooperation and Development (OECD), the benefits to farmers are also perceived as a good way to reduce the costs and market distortions of their existing farm support policies, which now total about US$320 billion a year. Moreover, whereas oil and coal are unevenly distributed among countries, all countries could generate some bioenergy from domestically grown biomass of one type or another, thereby helping to reduce their dependence on imported fossil fuels.